Enhanced-Textured-Powder Bi-2212/Ag Wire Development. (April 2019) - Kellams, J N; McIntyre, P; O'Quinn, K
Abstract: A new method for preparing Bi-2212/Ag multifilament wire is being developed. Bi-2212 fine powder is homogenously mixed with nanoparticle Ag and uniaxially compressed into square-cross-section rods. The rods are assembled into a silver matrix and drawn into monofilament wire, restacked, and drawn into multifilament wire. Heat treatment studies have been conducted to optimize parameters for a non-melt heat treatment. Transport current at 77 K and microstructure measurements have been made to guide the process development.